Penerapan Model Pembelajaran Learning Cycle 5e Dalam Meningkatkan Hasil Belajar PAI Di SMA Negeri 6 Lubuklinggau - Sujarwo, Sujarwo; Akip, Muhamad; Janna, Miftahul; Abadi, Candres (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2023)
Learning is essentially very related to how to attract students' interest in an active learning process. Interest is a major factor in developing student potential and has a very large influence on activity and success in learning. Students who have an interest in Islamic Religious Education subjects will study seriously, such as being happy in taking lessons and studying diligently both at school and at home because there is a special attraction to Islamic Religious Education subjects. If they do not have an interest in learning, students will not have enthusiasm in learning and may even find difficulties in learning Islamic Religious Education. In the learning process there are three main components that influence each other, namely (1) learning conditions, (2) learning methods, (3) learning outcomes. The research that the researchers carried out was a type of Classroom Action Research (PTK) or Classroom Action Research. PTK is a study that is relatively increasing, deepening, and improving and is carried out collaboratively. which is reflective by taking certain actions in order to improve and remember the quality of learning in the classroom aims to improve and improve the quality of lessons. .30%. Second, classically students who have completed learning from 35.30% pre-cycle and at the end of cycle II in this study students who obtained grades according to KKM reached 85.30%.